PENEGAKAN HUKUM ACARA PIDANA (UNDANG-UNDANG NOMOR 8 TAHUN 1981) DALAM TINDAK PIDANA CYBERCRIME DAMPAK DARI ERA GLOBALISASI - Renson Sinaga (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT  In order for the law to perform its functions properly, special efforts are called law enforcement. Law enforcement is a process undertaken to realize legal desires in order to become reality. Legal wishes here are interpreted as the minds of the legislator body formulated in the laws of law aimed at upholding justice. To enforce the Criminal Procedure Code there are several steps that must be passed, such as the formulation stage, namely the in-abstraction law enforcement stage conducted by the legislative body, this stage can also be called the stage of legislative policy. At this stage a rule is formulated. Application phase, which is the application stage of Criminal Procedure Law by law enforcement officers ranging from the police to the court This stage can also be called the Judicial wisdom. The execution stage, which is the concrete stage of the implementation of criminal by the criminal apparatus, this stage can also be referred to as the stage of executive or administrative wisdom. All stages of law enforcement are equally important in law enforcement efforts, but in practice law enforcement of the second and third stages plays a very important role, namely the application and execution of the Criminal Procedure Code, because the rules without application and execution is only a theory that does not mean what . Another thing that is not less important in the process of enforcing the Criminal Procedure Law is the community, the public should be aware that in the process of law enforcement is not the responsibility of the law enforcement apparatus alone, but it is the responsibility of the community in the effort to deal with and overcome various forms of crimes that harm and disturb society itself. Barriers to cybercrime crime are: Non-juridical Barriers The laziness of people reporting a crime, viewed as a whole 85% of crimes committed in the community are not reported. Juridical Barriers arising from the Police Samarinda Problems of proof, because in committing criminal acts cybercrime, the perpetrators always use false identity, so in this case the police is difficult to prove who the real perpetrator, except caught hands or seen directly. Especially for Indonesia, there has been no formulation of a new offense on cybercrime crimes, so it still uses the old formula that is all-under, so often have to use extensive interpretation.